Models for visual saliency in images and videos - Viswanath Gopalakrishnan (2011)
Multimedia data consisting of videos and images are in general very rich in content and carry lot of information. With the digital cameras and camcorders becoming easily available to consumers, the amount of information in the form of multimedia data stored and shared across web has increased exponentially. Human beings are normally interested only in a ’subset’ of this information available in images and videos, which they consider as salient. Given the huge amount of data to be processed, it is important to obtain information regarding the regions in an image or video which attract human attention so that the overhead of redundant data can be greatly reduced in multimedia applications. The detection of such salient regions or objects in images and videos is the objective of the proposed research work.